A systematic review of contributing factors of and solutions to electronic health record–related impacts on physician well-being. (1st February 2021) - Nguyen, Oliver T; Jenkins, Nyasia J; Khanna, Neel; Shah, Shivani; Gartland, Alexander J; Turner, Kea; Merlo, Lisa J
Abstract: Objective: Physicians often describe the electronic health record (EHR) as a cumbersome impediment to meaningful work, which has important implications for physician well-being. This systematic review ( 1) assesses organizational, physician, and information technology factors associated with EHR-related impacts on physician well-being; and ( 2) highlights potential improvements to EHR form and function, as recommended by frontline physicians. Materials and methods: The MEDLINE, Embase, CINAHL, PsycINFO, ProQuest, and Web of Science databases were searched for literature describing EHR use by physicians and markers of well-being. Results: After reviewing 7388 article, 35 ultimately met the inclusion criteria. Multiple factors across all levels were associated with EHR-related well-being among physicians. Notable predictors amenable to interventions include ( 1) total EHR time, ( 2) after-hours EHR time, ( 3) on-site EHR support, ( 4) perceived EHR usability, ( 5) in-basket burden, and ( 6) documentation burden. Physician recommendations also echoed these themes. Conclusions: There are multiple complex factors involved in EHR-related well-being among physicians. Our review shows physicians have recommendations that span from federal regulations to organizational policies to EHR modifications. Future research should assess multipronged interventions that address these factors. As primary stakeholders, physicians should be included in the planning and implementation of such modifications to ensure compatibility with physician needs and clinical workflows.